Effects of Intravenous Hcg Administration on Plasma Steroids in Breeding Sahiwal Bulls - Kumar, A.; Pandey, A. K.; Honparkhe, M.; Ahuja, A.; Bisla, A.; Singh, A. K.; Singh, P. (The Indian Journal of Animal Reproduction, 2021)
The present study was conducted to assess the response of intravenous administration of hCG on plasma testosterone, estradiol, dehydroepiandrosterone (DHEA) and estriol levels in breeding Sahiwal bulls. Six breeding Sahiwal bulls were injected intravenously with 1500 I.U hCG followed by blood sampling at an interval of every 15 minutes for 4 hours. Plasma testosterone, estradiol, DHEA and estriol were estimated and the values were calculated by elaborating the standard curve. It was observed that testosterone level declined within 15 minutes of hCG administration followed by gradual increase until 3h. Fluctuation among the DHEA levels at different time intervals were somewhat near to the basal levels and similar to testosterone. However, non-significant differences were observed in plasma estradiol and estriol following hCG administration. It was concluded that endocrine status of Sahiwal bulls could be assessed between 1.25 to 3 hours of 1500 IU of hCG administration.